First description of the male of the little-known ant mimicking spider genus Aetius O. Pickard-Cambridge (Araneae: Corinnidae) - Pakawin Dankittipakul (2018)
The ant mimicking spider genus Aetius O. Pickard-Cambridge, 1896 is known to consist of only two species restricted to the Oriental Region. The present article gives the first description of the male of this genus, based on a male and a female of A. nocturnus Deeleman-Reinhold, 2001 collected in an evergreen hill forest of Thailand. The genitalia of both sexes are illustrated.